PENGARUH MODERASI VISI STRATEGIK TERHADAP HUBUNGAN KETERLIBATAN STRATEGIK DENGAN PERSEPSI KETIDAKPASTIAN LINGKUNGAN, PERSEPSI KEKUATAN KOMPETITIF, KETERLIBATAN KERJA, DAN KOMITMEN ORGANISASIONAL (SUATU RENCANA STUDI PADA SMU DAN SMK SEKECAMATAN CILEUNGSI - Agus Fauzi (Jurnal Manajemen, 2022)
The study in this article aims to produce a model of research moderating impact of strategic vision to the relationship of strategic involvement with perception of environment uncertainty, perception of competitive strength, job involvement, and organizational commitment.  This article is a review of the literature, so that method being used is a literature review. This study is conducted by studying theories that have been established. The study also sourced and based on the results of previous research, especially empirical research results related to the variables that were studied in this article. In addition, if it is continued in empirical research, the study population are Head Master and Vice Head Master of SMU and SMK in Kecamatan Cileungsi Kabupaten Bogor. This article study produces a research model that explains the moderating impact of strategic vision to the relationship of strategic involvement with perception of environment uncertainty, perception of competitive strength, job involvement, and organizational commitment. Hypotheses include the following; moderating impact of strategic vision to relationship strategic involvement is positively related and significant to perception of environment uncertainty, perception of competitive strength, job involvement, and organizational commitment. Strategic vision moderate the relationship of strategic involvement with perception of environment uncertainty, Strategic vision moderates the relationship of strategic involvement with perception of competitive strength, job involvement, and organizational commitment.